Organic Farming: A brief summary - Parul (Universal Research Reports, 2017)
The furtherance of technology and progress in agriculture has empowered our country to furnish food security. But this technology negative effect also. That types of technology imbalanced our ecosystem. Under such status, dangerous earthly concerns have been verbalized regarding the use of heavy chemicals, pesticides and fertilizers in agriculture in footing of their negative effect on the human health and the environment. The chance of ‘Organic Agriculture’ is the only solution to nurture the land and to reproduce the soil by going back to our traditional method of farming i.e., free from chemicals, pesticides and fertilizers. This is a potential step for sustainable development by adopting not to use chemicals, synthetic materials, pesticides and generate hormones to produce high nutritional quality food and in appropriate quantity. This article provides an overview of organic agriculture in India.